LITERARY MAGAZINE: ITS SOCIAL-AND-CULTURAL MISSION AND FUNCTIONS IN THE LITERARY COMMUNICATION - Olga G. Shilnikova; Galina S. Belolipskaya (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2019)
The article analyzes the functions of the literary magazine in the current social-and-cultural space. The educational, communicative, creative, social-and-cultural potential of modern monthly publications is revealed. It is stated that multifunctionality is one of the most valuable typological features of national literary magazines. Over a long period of Russian journalism, culture, and history development it was this specificity that ensured the stability of this type of media. At the same time, multifunctionality is the key to the further literary journal evolution as a publication type. In the article the objective and subjective causes of the modern journals crisis are determined. Due to the specificity of the content, literary publications face serious troubles in adapting to new social-and-cultural reality that is losing its artistic literary centricity and to the media product functioning aspects in the digital age, when literary communication takes on a altered quality and different forms. These circumstances largely determine the instability of the typological profile and the functional paradigm of modern magazines. A comprehensive way of overcoming crisis phenomena is proposed. It is proved that the future of literary magazines consists in integrationinto the new information reality and the new media system, while maintaining its unique cultural functionality. It is important that each publication concretizes its typological model: its mission, tasks, place in the cultural space, target audience; ideological and substantial vector of literary, critical, publicistic discourses and ways of their representation, structural features, authors, directions of extrajournalistic sociocultural activities.